2023
DOI: 10.1186/s13293-023-00487-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-divergent effects on the NAD+-dependent deacetylase sirtuin signaling across the olfactory–entorhinal–amygdaloid axis in Alzheimer’s and Parkinson’s diseases

Abstract: Background Smell impairment is one of the earliest features in Alzheimer’s (AD) and Parkinson’s diseases (PD). Due to sex differences exist in terms of smell and olfactory structures as well as in the prevalence and manifestation of both neurological syndromes, we have applied olfactory proteomics to favor the discovery of novel sex-biased physio-pathological mechanisms and potential therapeutic targets associated with olfactory dysfunction. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…They studied the olfactory tracts of PD and AD patients. Overall, they found that the tangled SIRT (SIRT1-5) profile observed across the olfactory pathway-associated brain regions in AD and PD indicates differential NAD (+)-dependent deacetylase mechanisms between women and men [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…They studied the olfactory tracts of PD and AD patients. Overall, they found that the tangled SIRT (SIRT1-5) profile observed across the olfactory pathway-associated brain regions in AD and PD indicates differential NAD (+)-dependent deacetylase mechanisms between women and men [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead, to our surprise, it was SIRT1 inhibition that increased PFC-LTP in APP/PS1 female mice. These are results to be further clarified in the future, including an evaluation of potential sex-dependent differences in the action of sirtuins that was identified in some recent studies [ 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 96%
“…According to the Declaration of Helsinki, all assessments, post-mortem evaluations, and experimental procedures were previously approved by the Clinical Ethics Committee of Navarra Health Service (Study code: PI_2019/108). Post-mortem brain processing, extraction and fixation were performed as previously described (23). The neuropathological diagnosis was carried out according to the current neuropathological guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Protein extraction, sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS), MS/MS library generation, proteome quantitation and data analysis was performed as previously described (23). Mass-spectrometry data and search results files were deposited in the Proteome Xchange Consortium via the JPOST partner repository (https://repository.jpostdb.org) with the identifier PXD038061 for ProteomeXchange and JPST001921 for jPOST (for reviewers: https://repository.jpostdb.org/preview/1400199357636bce4231af5 Access key: 8609).…”
Section: Methodsmentioning
confidence: 99%